Surgery of Renovascular Hypertension: indications and results - Danza, Rómulo; Baldizán, Jorge; Olivera, Daniel; Navarro, Teodoro (Cirugía del Uruguay, 1980)
24 case series in wicli arterial hypertension was soled ·through surgical procedures and_ review of -various problems connected with renovascular hypertension.